The relationship between delivery and the PaO2/FiO2 ratio in COVID‐19: a cohort study. (20th August 2021) - Pineles, BL; Stephens, A; Narendran, LM; Tigner, MA; Leidlein, C; Pedroza, C; Mendez‐Figueroa, H; Sibai, BM
Abstract : Objective: To study the effect of delivery on the pO2 /FiO2 ratio (P/F ratio) in patients with COVID‐19‐related acute respiratory distress syndrome (ARDS) and to compare characteristics between delivered and undelivered pregnant patients with COVID‐19. Design: Retrospective cohort. Setting: Four hospitals in Houston, Texas. Population: Pregnant patients admitted to the hospital for COVID‐19. Methods: Among patients with ARDS who were delivered during their hospitalisation for COVID‐19, linear mixed models were used to investigate time trends before and after delivery of the P/F ratio. Patient characteristics were compared between patients delivered during their hospitalisation for COVID‐19 and those discharged undelivered. Main outcome measures: The P/F ratio, age, gestational age, length of stay and severity of illness, Results: Between 4 May 2020 and 26 July 2020, a total of 61 pregnant patients were admitted for COVID‐19. Baseline characteristics were similar between the study groups. Delivery occurred in 21 (34%) of patients during their hospitalisation for COVID‐19. Delivered patients had more severe disease and were admitted at a later gestational age than patients not delivered. Ten of these 21 patients (48%) were delivered preterm; of these, six were delivered due to complications of COVID‐19 and four were delivered for obstetric indications. In patients with ARDS who were delivered ( n = 17), the P/F ratio had a negative slope that improved after delivery. Conclusions: COVID‐19‐related ARDS in pregnancy requires multidisciplinary care and individualised decision‐making, but delivery slows the deterioration of the P/F ratio in these patients. Tweetable abstract: Delivery improves the P/F ratio in COVID‐19‐related ARDS, though individualised delivery management is needed. Tweetable abstract: Delivery improves the P/F ratio in COVID‐19‐related ARDS, though individualised delivery management is needed.